PELATIHAN KEPEDULIAN KARIER DI JURUSAN USAHA PERJALANAN WISATA SMKN 1 BANDUNG - Marlita Andhika Rahman (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2018)
INTRODUCTION Carelees attitude towards majors studied, cause he doesn,t have the variety of information work in the world of tourism, example tour guide a tourist attraction, but must have skill to match the feeling and lead the group it serves. Therefore it is very important for a business travel have concern for jobs in tourism. In this research, the researcher designed a training based on one important part of the orientation toward career choices in career maturity Super of awareness. It’s important for the teen subject to realize and axplore a variety of jobs in the tourism world for preparing career choice. METHOD The design research in this Career Awareness Training is quasi experimental using one group pre-test – post-test design to look at increasing the career awareness of student mjors business trip and travel in vocational high school. Subjects in this try out is the teen students who want to work after graduation school. Measurements conducted using questionnaires career awareness and guide observation as long training of career awareness.RESULTS Testing statitistic to measure knowledge will be done using Paired t-testt. Result of career awareness p-value (two tailed) = 0,007 koef.alpha (α) = 0.05. Statistic test result showed that the value of koef.alpha > p-value, it can be concluded that career awareness training affected on the increase of awareness for student majors business travel in vocational high school. CONCLUSION AND RECOMMENDATION The students understand competence of tour guides through career awareness training, add good value to knowledge, understanding the character of tourists and guiding planned trips. If it is to be used, it is good to have the training guidelines prepared need to be adjusted to the character and problems by the participants. Keywords: career maturity, orientation choice career, career awareness, awareness training, vocational school